Working together: Expanding the availability of naloxone for peer administration to prevent opioid overdose deaths in the Australian Capital Territory and beyond - Lenton, Simon; Dietze, P.; Olsen, A.; Wiggins, N.; McDonald, D.; Fowler, C. (Wiley-Blackwell Publishing Ltd., 2014)
Issue. Since the mid-1990s, there have been calls to make naloxone, a prescription-only medicine in many countries, available to heroin and other opioid users and their peers and family members to prevent overdose deaths. Context. In Australia there were calls for a trial of peer naloxone in 2000, yet at the end of that year, heroin availability and harm rapidly declined, and a trial did not proceed. In other countries, a number of peer naloxone programs have been successfully implemented. Although a controlled trial had not been conducted, evidence of program implementation demonstrated that trained injecting drug-using peers and others could successfully administer naloxone to reverse heroin overdose, with few, if any, adverse effects. Approach.In 2009 Australian drug researchers advocated the broader availability of naloxone for peer administration in cases of opioid overdose. Industrious local advocacy and program development work by a number of stakeholders, notably by the Canberra Alliance for Harm Minimisation and Advocacy, a drug user organisation, contributed to the rollout of Australia’s first prescription naloxone program in the Australian Capital Territory (ACT). Over the subsequent 18 months, prescription naloxone programs were commenced in four other Australian states. Implications. The development of Australia’s first take-home naloxone program in the ACT has been an ‘ice-breaker’ for development of other Australian programs. Issues to be addressed to facilitate future scale-up of naloxone programs concern scheduling and cost, legal protections for lay administration,prescribing as a barrier to scale-up; intranasal administration, administration by service providers and collaboration between stakeholders.